New species and records of the Neotropical genus Cyrnellus (Trichoptera: Polycentropodidae) and the re-establishment of C. minimus and C. marginalis - Martín, Paola A. Rueda; Gibon, Francois-Marie; Sganga, Julieta V. (Zootaxa, 2021)
Cyrnellus is a small genus of Polycentropodidae distributed in the Nearctic and Neotropical regions, absent from the Chilean subregion. Two new species are here described: C. boliviensis sp. nov. and C. guyanensis sp. nov. Cyrnellus minimus Banks 1913 considered as a junior synonym of Cyrnellus fraternus (Banks 1905) by Flint (1971) and C. marginalis (Banks 1930) considered as a junior synonym of Cyrnellus fraternus by Flint (1964) are revalidated at the specific level. We provide a key and illustrations for adult males and nine new country records for Bolivia.